Buccal Mucosal Smears Cytomorphology among Active and Passive Cigarette Smokers in Abeokuta City, Ogun State, Nigeria (African Journal of Biomedical Research, 2023)
Cigarette smoke is a well-known main risk factor for cancer related early death. Exposure to cigarette smoke by both active and passive smokers increases the incidence of infections and causes atypical changes. This study aimed at examining the cytomorphological features of buccal mucosal smears of active, passive cigarette smokers and non-smokers. About 290 subjects were recruited for this study, of which 220 were active cigarette smokers, 20 were passive cigarette smokers and 50 were non-smokers. Sterile Ayre’s spatulas were used to collect buccal mucosa samples from each subject and smeared immediately on 3 clean frosted slides, which were fixed immediately with 95% Methanol for at least 30 minutes before they were stained using Papanicolaou, Giemsa and Heamatoxylin & Eosin techniques respectively. Stained smears were viewed with the microscope to examine their cytomorphological features. Cytological features such as pleomorphism, hyperchromatism, micronuclei, fungal infection and increased nuclei-cytoplasmic ratio were observed in increased severity in the buccal mucosa smears of active cigarette smokers when compared with the Passive cigarette smokers and the non-smokers.  Oral exfoliative cytology is a non-invasive, low-cost test that should be advocated in cigarette smokers for early detection of any precancerous diagnosis.
Keywords: Buccal mucosa; cigarette; giemsa; papanicolaou; pleomorphism